Effects of repetitive galvanic vestibular stimulation on spatial neglect and verticality perception—a randomised sham-controlled trial. Issue 7 (3rd October 2018) - Volkening, Katharina; Kerkhoff, Georg; Keller, Ingo
ABSTRACT: Recent evidence shows that bipolar galvanic vestibular stimulation (GVS) with the cathode on the left (CL) or right (CR) mastoid ameliorates spatial neglect, extinction and verticality perception transiently and partly permanently. However, no randomised controlled trial evaluated the long-term effects of repetitive GVS in comparison to sham-GVS on exploration and verticality perception. To compare the effects of CL-GVS, CR-GVS and Sham-GVS on spatial exploration and verticality perception in right-hemispheric stroke patients with left neglect we conducted a randomised controlled trial with minimisation. Twenty-four patients completed 10–12 training sessions on a daily basis, 5 days/week. The CL-and CR-GVS group received 20 min of stimulation at 1.5 mA, the Sham-GVS group only 30 s of CL-GVS. Simultaneously, all patients performed a standard therapy of smooth pursuit eye movement training (SPT) followed by visual scanning training (VST). Outcome measures (Neglect test, visuo-tactile search task, subjective visual and tactile vertical) were assessed before and immediately after the intervention and at 2- and 4-week follow-ups. Our results show that neither our standard therapy nor the combination of standard therapy and GVS improved neglect symptoms significantly. The reasons for our non-significant results are discussed.